1999
DOI: 10.1046/j.1523-1755.1999.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and methionine metabolism in ESRD: A stable isotope study

Abstract: The conversion of homocysteine to methionine is substantially (approximately 30%) decreased in hemodialysis patients, whereas transsulfuration is not. Decreased remethylation may explain hyperhomocysteinemia in ESRD. This stable isotope technique is applicable for developing new and effective homocysteine-lowering treatment regimens in ESRD based on pathophysiological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
2
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 28 publications
(10 reference statements)
3
92
2
2
Order By: Relevance
“…On the other hand, a lower rate of plasma Hcy clearance was observed in HHcy in renal patients compared with healthy persons, which suggests a role for the kidney in the elimination of this aminothiol (33 ). The remethylation of Hcy to methionine is lower in hemodialysis patients (34 ). In addition, Hcy remethylation was shown to be impaired in dialysis patients despite serum concentrations of vitamin B 12 and folate being well above those found in the general population (4 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a lower rate of plasma Hcy clearance was observed in HHcy in renal patients compared with healthy persons, which suggests a role for the kidney in the elimination of this aminothiol (33 ). The remethylation of Hcy to methionine is lower in hemodialysis patients (34 ). In addition, Hcy remethylation was shown to be impaired in dialysis patients despite serum concentrations of vitamin B 12 and folate being well above those found in the general population (4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most (85% to 100%) patients with end-stage renal disease have hHcys. 15 It has been indicated that the hHcys in end-stage renal disease is induced by the abnormality of Hcys metabolism in the kidneys but not simply because of reduced glomerular filtration of Hcys. 10,15,16 Although these observations suggest a major role for the kidneys in Hcys elimination, the role of the kidneys in the development of hHcys and the possible mechanisms leading to impaired clearance of Hcys by the kidneys have yet to be elucidated.…”
mentioning
confidence: 99%
“…13 CO 2 arises either from transsulfuration of HCY to cysteine, decarboxylation of AdoMET or transamination, and subsequent decarboxylation of MET. Decarboxylation of AdoMET is a minor pathway in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of MET and its investigation with stable isotopes. If L-[ 2 H 3 -methyl-1- 13 C]methionine (m/z ϭ ϩ 4) enters the MET cycle, the methyl label will get lost during transmethylation from AdoMET to AdoHCY. Remethylated MET then can be detected in plasma with a mass of m/z ϭ ϩ 1.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation